Hungarian government cuts funding for priority Olympic sports due to COVID-19 - Houston, M. (2020)
The Hungarian Government is making cuts of around HUF 5.7 billion (£14.8 million/$19.3 million/€16.5 million) to the budgets for the nation's top Olympic sports due to the COVID-19 pandemic.